1996
DOI: 10.1111/j.0022-3646.1996.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

CYANOBACTERIAL BUOYANCY REGULATION: THE PARADOXICAL ROLES OF CARBON1

Abstract: In stratified lakes, dominance of the phytoplankton by cyanobacteria is largely the result of their buoyancy and depth regulation. Bloom‐forming cyanobacteria regulate the gas vesicle and storage polymer contents of their cells in response to interactive environmental factors, especially light and nutrients. While research on the roles of nitrogen and phosphorus in cyanobacterial buoyancy regulation has reached a consensus, evaluations of the roles of carbon have remained open to dispute. We investigated the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…2d) revealed enhanced biomass of Anabaena during longlasting stratified periods, whereas Microcystis was only found during short stratified periods of 1-2 weeks in duration. A decrease in buoyancy in several cyanobacteria genera, including Microcystis, under N and P limitation has been consistently reported from numerous studies (Konopka et al 1987;Klemer et al 1996). Thus, under Nlimiting conditions, such as those observed in Mü ggelsee (Wagner and Adrian 2009), N-fixing species such as Anabaena gain an advantage over non-N-fixing species of Microcystis.…”
Section: Discussionmentioning
confidence: 57%
“…2d) revealed enhanced biomass of Anabaena during longlasting stratified periods, whereas Microcystis was only found during short stratified periods of 1-2 weeks in duration. A decrease in buoyancy in several cyanobacteria genera, including Microcystis, under N and P limitation has been consistently reported from numerous studies (Konopka et al 1987;Klemer et al 1996). Thus, under Nlimiting conditions, such as those observed in Mü ggelsee (Wagner and Adrian 2009), N-fixing species such as Anabaena gain an advantage over non-N-fixing species of Microcystis.…”
Section: Discussionmentioning
confidence: 57%
“…Chien et al 2013). Far fewer studies have concentrated on the nutrient response, and they report a consistent decrease in buoyancy under N and P limitation and a buoyancy increase under N and P replenishment (Klemer et al 1996;Brookes and Ganf 2001;Chu et al 2007). In natural conditions, Bormans et al (1999) combined field observations from several Australian systems with studies reported in the literature to show that no field studies reported evidence for population migration to sufficient depth to reach nutrients in stratified systems.…”
Section: Buoyancy Regulationmentioning
confidence: 99%
“…However, competition for inorganic carbon is conceptually and experimentally more complex. Although earlier studies suggested that the ability of cyanobacteria to thrive and become dominant at low DIC concentration can be attributed to their CCM and competitive advantage for CO 2 , experimental evidence for this is limited (Shapiro, 1990;Klemer et al, 1996;Badger et al, 2006). Nakano et al (2003) found that Microcystis spp.…”
Section: Discussionmentioning
confidence: 99%